Pluronic and Chitosan based in situ gel system for periodontal application - Gupta, Himanshu; Sharma, Aarti; Shrivastava, Birendra (Asian Journal of Pharmaceutics (AJP), 2014)
Aim of this paper is to develop and evaluate a physiologically activated in situ gel for local periodontal application. The gel, when at formulation pH and temperature (pH 6, 25°C) will be at liquid form which will be converted to gel at body pH and temperature (pH 7.4, 37°C) showing ease of administration and prolonged duration of action. Chitosan which was both mucoadhesive as well as pH simulative polymer was used in combination with pluronic F-127 which is a temperature simulated gelation polymer. Prilocaine hydrochloride was used as model drug to check the efficacy of the developed in-situ gel system. Different combination of Chitosan and pluronic F-127 were tested and final combination of 0.5% w/v and 10% w/v of Chitosan and pluronic F-127 respectively were selected and further evaluated for parameters like physicochemical properties, viscosity, gelation pH, gelation temperature, in-vitro release, sterility testing and stability testing. The system thus developed was found to be clear and have good viscosity with prolonged release at pH 7.4 and 37°C. The formulation can be easily packaged and sterilized with method employed. As per ICH guidelines gel was found to be stable and a shelf life of 2 years was assigned to the formulation.